ANALISIS PERBEDAAN VERBA AMARU DAN NOKORU - Nindya, Elizabeth Ika Hesti (IZUMI, 2017)
Japanese has specific vocabulary. Unlike Indonesian language that has more general vocabulary. When translated into Indonesian, there are several Japanese word that have the same or synonymous meaning. There are some words that can be selected to show a situation in Japanese. Amaru and nokoru is this type of word in Japanese. Amaru and nokoru have a same meaning if it translated in Indonesian. Which is ‘sisa’. So in this study will be discussed more about the characteristics of these verbs. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor